2017
DOI: 10.1177/1010428317699796
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA-MALAT1-mediated Axl promotes cell invasion and migration in human neuroblastoma

Abstract: Overexpression of Axl has been noted to correlate with several human cancers. However, the regulatory mechanisms and effects of Axl in human neuroblastoma development remain unclear. Here, we explore the expression of Axl in neurobalstoma and related upstream regulatory mechanisms of invasion and migration. We found that Axl was overexpressed in metastatic neuroblastoma tissues and positively associated with long non-coding RNA metastasisassociated lung adenocarcinoma transcript 1. Meanwhile, our data suggeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…On the other hand, several studies showed that the expression of MALAT1 is downregulated in glioma [27], colorectal cancer [28], and breast cancer [29,30]. Previous in vitro and xenograft studies demonstrated that MALAT1 promotes cell proliferation, migration, tumor growth, metastasis, and chemoresistance [31,32,33,34,35,36,37]. In contrast, other studies reported that MALAT1 inhibits cell proliferation, tumor growth, invasion, and epithelial-mesenchymal transition (EMT) [27,28,30,38,39,40].…”
Section: Is Malat1 a Metastasis Promoter Or A Metastasis Suppressor?mentioning
confidence: 99%
“…On the other hand, several studies showed that the expression of MALAT1 is downregulated in glioma [27], colorectal cancer [28], and breast cancer [29,30]. Previous in vitro and xenograft studies demonstrated that MALAT1 promotes cell proliferation, migration, tumor growth, metastasis, and chemoresistance [31,32,33,34,35,36,37]. In contrast, other studies reported that MALAT1 inhibits cell proliferation, tumor growth, invasion, and epithelial-mesenchymal transition (EMT) [27,28,30,38,39,40].…”
Section: Is Malat1 a Metastasis Promoter Or A Metastasis Suppressor?mentioning
confidence: 99%
“…MALAT1 regulates endothelial cell function and vessel growth (Michalik et al, ). MALAT1 promotes cell migration and invasion by upregulating the gene expression of latent transforming growth factor beta binding protein 3 (LTBP3) and Axl (Bi et al, ; Hou et al, 2017). MALAT1 represses the expression of E‐cadherin by associating with suppressor of zeste 12 (suz12), thereby regulating EMT (Fan et al, ).…”
Section: Physiopathological Role Of Malat1mentioning
confidence: 99%
“…LncRNAs are involved in many biological processes, with LncRNA-MALAT1 and GAS5 being reported to mediate cell invasion, migration, and apoptosis in human neuroblastoma [ 34 , 35 ]. The lnc-LAMC2–1:1 polymorphism is located in the LAMC1 gene and close to the LAMC2 gene.…”
Section: Discussionmentioning
confidence: 99%